Head of State Liability for International Crimes ICC Prosecution of Duterte for Crimes Against Humanity. - Ghanar, Muhammad (JUSTICES: Journal of Law, 2025)
This research aims to analyze the liability of former heads of state for international crimes, focusing on the International Criminal Court’s (ICC) prosecution of Rodrigo Duterte for crimes against humanity. Using normative juridical methods with a case study approach, this paper examines the applicability of international criminal law principles, particularly individual accountability, complementarity, and jurisdiction, in Duterte’s case. The study emphasizes that despite the Philippines' withdrawal from the Rome Statute in 2019, the ICC retains jurisdiction over crimes committed while the country was a State Party. The research concludes that the ICC’s issuance of an arrest warrant for Duterte on March 11, 2025, affirms that former heads of state are not immune from prosecution for grave international crimes. This case sets a significant precedent in Southeast Asia and demonstrates the importance of international cooperation to overcome challenges related to state sovereignty and jurisdiction. It further highlights the ICC's critical role in upholding the rule of law and providing justice for victims of human rights violations